Association between periodontitis and heart failure in the general population. (13th September 2022) - Walther, Carolin; Wenzel, Jan‐Per; Schnabel, Renate B.; Heydecke, Guido; Seedorf, Udo; Beikler, Thomas; Borof, Katrin; Nikorowitsch, Julius; Schrage, Benedikt; Blankenberg, Stefan; Twerenbold, Raphael; Zeller, Tanja; et al.
Abstract: Aims: Data on the association between periodontitis and preclinical cardiac alterations remain scarce. The aim of the current study is to determine if periodontitis is associated with morphological and functional cardiac changes measured by transthoracic echocardiography as well as different heart failure (HF) phenotypes. Methods: Participants from the population‐based Hamburg City Health Study [ClinicalTrial.gov (NCT03934957)], who underwent transthoracic echocardiography and periodontal screening were included. Periodontitis was classified according to Eke and Page (none/mild, moderate, severe). The 2021 ESC HF guidelines were applied and HF was classified into HF with preserved ejection fraction (HFpEF, ejection fraction ≥50%), HF with mid‐range and reduced ejection fraction [HF(m)rEF, ejection fraction <50%], and HF in general [HFpEF and HF(m)rEF]. Due to limited size, all subjects with LVEF <50% and symptoms or signs of HF were classified as HF with reduced and mildly reduced ejection fraction [HF(m)rEF]. Results: Within 6209 participants with full periodontal examination, we identified an overlap of n  = 167 participants with periodontitis and HF. Participants with severe periodontitis showed a higher burden of cardiovascular risk factors (men at advanced age, diabetes mellitus, hypertension) when compared with participants with none/mild periodontitis. After adjustment for age, sex, body mass index, smoking, diabetes, hypertension, atrial fibrillation, and coronary artery disease, severe periodontitis was significantly associated with HF(m)rEF (odds ratio: 3.16; 95% CI: 1.21, 8.22; P  = 0.019), although no association was found for HFpEF and HF in general. Conclusions: The current study demonstrated that severe periodontitis was significantly associated with HF(m)rEF, although no relevant associations were found with HFpEF and HF in general as well as echocardiographic variables. The results implicate a potential target group, who need special attention from cooperating physicians and dentists. Future studies are warranted to verify whether systemic inflammation could be the link between the two diseases.